Cyclic voltammetry studies of biotoxins on nanostrutured screen printed electrodes - Teixeira, Cecília (2011)
The methods of analysis recognized for the detection of biotoxins marine in bivalve live molluscs have been modified by the European Commission 15/2011 in January 10 (2011) substituting the Regulation (CE) n º 2074/2005. Concurrently, bioassay's method in mice will not be able to continue used after December 31, 2014, for what it will be necessary that the different laboratories that nowadays carry out these biotoxin analyses, should equip adequately to be able to realize the pertinent controls. In this context, it will be necessary to develop sensitive/selective/cheap methods of analysis with robust instruments to obtain the indispensable requirements to be able to carry out the determination of the marine biotoxins with lower limits of detection (LOD) and to validate them with the standard AOAC method based on high performance liquid chromatography (HPLC)[1]. With this aim, we present the preliminary results of our work on the development of an electrochemical sensor based on the direct interaction between domoic acid (DA) and a “Screen Printed” Carbon Electrode (SPCE) modified with multi-walled carbon nanotubes (MWCNTs) with acidic (-COOH) functionalities (Figure 1). In these experiments, the voltammetric response of DA is controlled by its adsorption to the nanostructured electrode surface. The concentrations range tested were in the range of ng/l. The influence of several experimental parameters is studied to optimize the uptake processes. Figure 1. “Screen Printed” Carbon Electrode (SPCE) modified with multi-walled carbon nanotubes (MWCNTs) with acidic (-COOH) functionalities used for the electrochemical studies of Domoic Acid (DA) The methodology employed in this study will be extending to other ones biotoxins and to different types of nanostructured electrode surface upon incorporation of other nanomaterials and nanostructures such as nanoparticles (NPs). Acknowledgements Financial support from AECID-PCI Mediterráneo (A/031592/10). The authors thank to Ana Gago Team (UVigo) for their kind help and DA gift References [1] Gago-Martinez A. et al.,Chromatographia, 53 (2001) S231-S235.